The Hubungan Kesadaran Diri dengan Prokrastinasi Penyelesaian Skripsi pada Mahasiswa di Fakultas Olahraga dan Kesehatan UNG - Rachmawaty D. Hunawa; Tasmi S. Djafar; Reynaldi Niode (An Idea Health Journal, 2025)
Academic procrastination is known as behavior of delaying the completion of tasks, especially in completing a thesis, which can have a negative impact on students' academic achievement. The purpose of this study is to analyze the relationship between self-awareness and academic procrastination in completing a thesis in students at the Faculty of Sports and Health, Gorontalo State University. This study used a correlational research method with a crosssectional design. The research sample consisted of 212 final year students, selected using the proportionated stratified random sampling technique. Data were collected using a questionnaire that included the variables of self-awareness with academic procrastination. The results of the analysis showed that there was a significant relationship between self-awareness and academic procrastination, (p <0.05). Students who have good self-awareness tend to show lower levels of procrastination. The conclusion of this study emphasizes the importance of developing self-awareness skills in helping students overcome academic procrastination behavior, especially in completing a thesis. Therefore, it is recommended that there be a self- development and self-awareness program for students, so as to enhance their study effectiveness and accelerate the completion of their final assignments.